Use of infographics among selected libraries in Quezon City an exploratory study - Samson, Patricia B.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
Aside from its purpose to inform the users about the different services and collections of the library, a library instruction also supports the life-long learning of its users. Library instruction programs are thus expected to adapt to newer and more effective instruction methods. The study focused on the librarians' preferences in using and creating infographics, a form of data visualization, in library instruction. The study sought to assess the instructional materials used for library instruction; the types of infographics used in library instructions; the preferences of participants in creating and using infographics.
A total of 30 licensed librarians were considered to participate in the study and answer the survey questionnaires. The librarians came from four different types of libraries: academic, school, public, and special libraries.
The data gathered showed that the use of infographics among selected librarians in Quezon City was observed to be true a certain extent, with fewer librarians to have actually used and created infographics for library instruction compared to those who have not.
The use of PowerPoint presentations as instructional materials is the most common among all the respondents. The use of infographics for library instruction was observed to be more common for librarians under the Technical and Reference sections of the library and for librarians working for Academic libraries.
The results suggested that regardless of the participants' differences in demographics (age, educational background (undergraduate and postgraduate degrees), and training applicable to the creation of visual resources), most of them consider the use and creation of infographics for library instruction. In terms of the creation of infographics, majority of the participants consider creating the visual resource with the help of other library staff. With the use of infographics, 43.33% of them indicated that they have used infographics in the past instruction programs. Using infographics found online for library instruction sessions was also considered by the majority of the participants. The most commonly used type of infographics was the statistical based infographics. The three most common factors affecting the librarians' use of infographics are the following in order: 1.) To improve presentation of a task (e.g. using information resources for reports, presentations, etc.) 87.5%; 2.) Ease of understanding the information presented, 54.17%; and 3.) Ease of finding needed information, 54.17%. For the factors affecting their decision to not use the infographics for library instruction sessions, the three most common responses of the 29 participants who answers item 14 (Q14) are the following in order: 1.) Preference to use other types of visual resources, 37.93%; 2.) Unaware of the existence of infographics as visual resources, 27.59%; 3.) Difficulty to coordinate visual images in the infographics to information (e.g. difficulty to distinguish ads, website links, web pages, etc.) and Lack of knowledge in ethical practices with using retrieved information (e.g. citation), both 24.24%.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Library orientation -- Philippines -- Quezon City; Visual education -- Philippines -- Quezon City; Librarians -- Philippines -- Quezon City